Self-contextual network management system. (5th December 2006) - Cheng, Lawrence; Galis, Alex; Lazanakis, Antonis J.; Karetsos, George; , Spyros Denazis
Self-adaptation to changes in network context or self-contextual functionality refers to the capability of network nodes to dynamically reconfigure themselves in changing heterogeneous networking environments, in which new services and protocols will be rapidly created and deployed on demand. A novel programmable architecture, called the Future Active IP Networks (FAIN) node, is presented to address the described issues.